-9-2f=5f-23

Simple and best practice solution for -9-2f=5f-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9-2f=5f-23 equation:


Simplifying
-9 + -2f = 5f + -23

Reorder the terms:
-9 + -2f = -23 + 5f

Solving
-9 + -2f = -23 + 5f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-5f' to each side of the equation.
-9 + -2f + -5f = -23 + 5f + -5f

Combine like terms: -2f + -5f = -7f
-9 + -7f = -23 + 5f + -5f

Combine like terms: 5f + -5f = 0
-9 + -7f = -23 + 0
-9 + -7f = -23

Add '9' to each side of the equation.
-9 + 9 + -7f = -23 + 9

Combine like terms: -9 + 9 = 0
0 + -7f = -23 + 9
-7f = -23 + 9

Combine like terms: -23 + 9 = -14
-7f = -14

Divide each side by '-7'.
f = 2

Simplifying
f = 2

See similar equations:

| 7c+3(c-4)=8 | | 111=-12x+15 | | 30-15w=2w-6 | | 2x+2+7=16 | | -2x+4=ax+b | | 6x-5=7x-13 | | 1+2x=-7+x | | 4(2x+1)=8x+11 | | 6x-6+x-3=2x-1 | | 3(2x-5)=81 | | 5x+87=54 | | -7n+8=15 | | 2x-10=2x+20 | | z-16=-15 | | 5z-2=4z | | 8n-32+8n=-128 | | 2+16c=52 | | 3.6(2p+4)=3(2-3p) | | 6-3a=10a | | (k-6)-2=10 | | y=2x^2-3x-4 | | xcube=64 | | 1+8x+2x=2+6x+2-7 | | 18a^2-15a-63=0 | | -4(3x+4)=-88 | | 6a+3=4a-1 | | 5w-13-3w=15 | | 120=-6(4-6n) | | ln(2-3x)=1 | | 1=3w-6 | | -10=-4p-6p | | 57t-64-(7-20t)= |

Equations solver categories